Lactate in the tumor microenvironment: A rising star for targeted tumor therapy - Li, Zhangzuo; Wang, Qi; Huang, Xufeng; Yang, Mengting; Zhou, Shujing; Li, Zhengrui; Fang, Zhengzou; Tang, Yidan; Chen, Qian; Hou, Hanjin; Li, Li; Fei, Fei; et al. (Frontiers in Nutrition, 2023)
Metabolic reprogramming is one of fourteen hallmarks of tumor cells, among which aerobic glycolysis, often known as the "Warburg effect," is essential to the fast proliferation and aggressive metastasis of tumor cells. Lactate, on the other hand, as a ubiquitous molecule in the tumor microenvironment (TME), is generated primarily by tumor cells undergoing glycolysis. To prevent intracellular acidification, malignant cells often remove lactate along with H+, yet the acidification of TME is inevitable. Not only does the highly concentrated Lactate within the TME serve as a substrate to supply energy to the malignant cells, but it also works as a signal to activate multiple pathways that enhance tumor metastasis and invasion, intratumoral angiogenesis, as well as immune escape. In this review, we aim to discuss the latest findings on lactate metabolism in tumor cells, particularly the capacity of extracellular lactate to influence cells in the tumor microenvironment. In addition, we examine current treatment techniques employing existing medications that target and interfere with lactate generation and transport in cancer therapy, as well as combination therapeutic tactics including nanomaterials. New research shows that targeting lactate metabolism, lactate-regulated cells, and lactate action pathways are viable cancer therapy strategies.